Identifikasi Potensi dalam Upaya Perencanaan Masterplan Desa Wisata Kebondalem Kidul, Klaten, Jawa Tengah - Slamet Subiyantoro; Tiara Meilania Subekti; Shalma Widyawati; Arkan Zuhdi; Devanda Rizky Pratama; Risna Cahyani; Kanaka Hadan Balindra Riyanda; Marcelio Adwivieri Satriatama; Dwi Wahyu Kurniawan; Sabillah Ma’ruf; Bregas Widi Prasetyo (Jurnal Pengabdian Masyarakat Nusantara, 2025)
Kebondalem Kidul Village, located in Klaten Regency, Central Java, holds promising tourism potential. However, this potential has not been well mapped, resulting in the absence of a comprehensive development planning scheme. To help the village grow and direct the development of necessary infrastructure and facilities, the Kebondalem Kidul Village Government collaborated with a KKN team from Sebelas Maret University (UNS) to create a masterplan aimed at providing guidance on how to manage the village's tourism potential. The research method used in this study is descriptive-exploratory, which helps to describe a phenomenon and present data and facts chronologically based on field findings. The data collected was then processed using the triangulation method. This technique analyzes data from various sources, including observation data, interviews, and secondary data. The use of this analysis technique helps to combine all data to produce accurate and comprehensive conclusions. The results of the study show that Kebondalem Kidul Village has various cultural potentials that are used as references in designing the cultural tourism village masterplan. The identification of potential in Kebondalem Kidul Village led to the creation of a tourism map as a form of community service.